Body composition and bone mineral density in athletes with a physical impairment - Cavedon,Valentina; Sandri,Marco; Peluso,Ilaria; Zancanaro,Carlo; Milanese,Chiara (PeerJ, 2021)
Background The impact of the type and the severity of disability on whole-body and regional body composition (BC), and bone mineral density (BMD) must be considered for dietary advice in athletes with a physical impairment (PI). This study aimed to investigate the impact of the type and the severity of disability on BC, the pattern of distribution of fat mass at the regional level, and BMD in athletes with a PI. Methods Forty-two male athletes with spinal cord injury (SCI, n = 24; age = 40.04 ± 9.95 years, Body Mass Index [BMI] = 23.07 ± 4.01 kg/m2) or unilateral lower limb amputation (AMP, n = 18; age = 34.39 ± 9.19 years, BMI = 22.81 ± 2.63 kg/m2) underwent a Dual-Energy X-Ray Absorptiometry scan. Each athlete with a PI was matched by age with an able-bodied athlete (AB, n = 42; age = 37.81 ± 10.31 years, BMI = 23.94 ± 1.8 kg/m2). Results One-Way Analysis of Variance showed significant differences between the SCI, AMP and AB groups for percentage fat mass (%FM) (P < 0.001, eta squared = 0.440). Post-hoc analysis with Bonferroni’s correction showed that athletes with SCI had significantly higher %FM vs. the AMP and AB groups (25.45 ± 5.99%, 21.45 ± 4.21% and 16.69 ± 2.56%, respectively; P = 0.008 vs. AMP and P < 0.001 vs. AB). The %FM was also significantly higher in the AMP vs. the AB group (P < 0.001). Whole-body BMD was negatively affected in SCI athletes, with about half of them showing osteopenia or osteoporosis. In fact, the mean BMD and T-score values in the SCI group (1.07 ± 0.09 g/cm2 and −1.25 ± 0.85, respectively) were significantly lower in comparison with the AB group (P = 0.001 for both) as well as the AMP group (P = 0.008 for both). The type of disability affected BC and BMD in the trunk, android, gynoid and leg regions in SCI athletes and the impaired leg only in AMP athletes. Conclusions In conclusion, the type of disability and, partly, the severity of PI impact on BC and BMD in athletes with a PI. Nutritionists, sports medicine doctors, clinicians, coaches and physical conditioners should consider athletes with SCI or AMP separately. Athletes with a PI would benefit from specific nutrition and training programs taking into account the type of their disability.
Keywords: DXA; Spinal cord injury; Lower limb amputation; Fat-mass to lean-mass ratio; Bone mineral density; Percentage fat mass; Body composition